5-Aminolevulinic Acid Improves Morphogenesis and Na+ Subcellular Distribution in the Apical Cells of Cucumis sativus L. Under Salinity Stress - Wu, Yue; Liu, Na; Hu, Linli; Liao, Weibiao; Tang, Zhongqi; Xiao, Xuemei; Lyu, Jian; Xie, Jianming; Calderón-Urrea, Alejandro; Yu, Jihua (Frontiers in Plant Science, 2021)
Soil salinity in worldwide has caused damages of plants and reduction of output. A natural plant growth regulator, 5-aminolevulinic acid (ALA), has been proved to have promotive role in plant growth under abiotic stress conditions. In the present study, the effects of exogenously applied ALA (25 mg L-1) on root architecture and Na+ distribution in cucumber (Cucumis sativus L.) seedlings under moderate NaCl stress (50 mmol L-1) were assessed. The results showed that exogenous ALA improved root length, root volume, root surface area and cell activity in the root tips, which were inhibited under salt stress. In addition, salinity stress individually increased the subcellular Na+ contents, such as cell wall, nucleus, plastid and mitochondria, however, they were all decreased when treated with ALA; the only exception to this was the soluble fraction. The analysis of molecular biology revealed that application of ALA up-regulated the both SOS1 and HA3 in transcriptional and translational levels, suggesting that the excretion of Na+ into the cytoplasm cloud be promoted by exogenous ALA. Meanwhile, exogenously applied ALA also up-regulated the gene and protein expression of NHX1 and VHA-A under salinity stress, which suggested that the compartmentalization of Na+ to the vacuole has been enhanced. Overall, exogenous ALA could mitigates damages caused by NaCl in cucumber by enhancing the Na+ redistribution and increasing the cytoactity of root cell.